Analisis Menurunnya Minat Beli Nasabah Pada Pelelangan Barang Jaminan Emas di Pegadaian Syariah (Studi Kasus: Cabang Blauran Surabaya) - Latif, Sriyanti Dewi; Afandi, Nihro (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Interest is the customer's encouragement or desire to buy the goods they want without the desire, desire and encouragement of the customer's interest not being realized, where interest can also be seen from the object and quality of the goods they want to buy. Meanwhile, the Auction process itself is the sale of goods in public which is preceded by an effort to gather interested parties through announcements made by and carried out in front of the auction official with an optimal price offer through verbal up-and-down or down-down and/or written bidding. Usually, items that have entered the auction date at the Sharia Pawnshop, Blauran Surabaya Branch, notify the customer that the collateral is due, if the customer of the collateral does not make an extension or confirmation, the pawnshop will auction the collateral. The auction at the Blauran Surabaya branch of the sharia pawn shop is different from the auction in general, where the price of the auction items is determined by the pawnshop by looking at the market price and the central price.The aim of this research is to determine the decline in customer interest in purchasing auctioned items and how the auction process occurs at the Blauran branch of Surabaya sharia pawn shop. In this research method, the researcher uses a type of field research using qualitative research methods. Meanwhile, in collecting data, researchers used interviews, documentation in the form of photos and sound recordings. The results of the research concluded that the decline in purchases of auctioned goods was due to customers considering that the auctioned goods were used by other people, the models looked old, the quality of the goods being auctioned and the marketing of the pawnshop itself was not capable enough to attract customer interest. , in terms of the process of carrying out the auction items themselves, it can be seen from the time of the auction, the auction mechanism, the items that have been included in the auction list and the Rahin (customer) wants to redeem, Information on the maturity date to the Rahin (customer), Notification to the Rahin (customer) whose items will be auctioned.